Direct and indirect regulation of bone metabolism by lactoferrin - Wu, Yangyang; Zhang, Cunxin; Lv, Chaoliang (Frontiers in Endocrinology, 2025)
Lactoferrin exerts positive regulation on bone metabolism through both direct and indirect pathways. Directly, it modulates osteoblasts, osteoclasts, and chondrocytes via factors such as insulin-like growth factor (IGF), low-density lipoprotein receptor-associated protein (LRP), transforming growth factor β (TGF-β) receptor, and bone morphogenetic proteins (BMPs). These factors promote differentiation and inhibit apoptosis of bone metabolism-related cells through signaling pathways including the receptor activator of nuclear factor kappa-B (RANK), its ligand RANKL, and osteoprotegerin (OPG), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK), macrophage colony-stimulating factor (M-CSF), Ca2+, phosphoinositide 3-kinase/protein kinase B (PI3K/Akt), Wnt/β-catenin, BMP-2/Smad, and TGF-β. Indirectly, lactoferrin influences skeletal muscle, energy metabolism, intestinal microbiota, immune function, and calcium-phosphorus homeostasis, all of which positively affect bone metabolism. In-depth research into lactoferrin-derived peptides and their complexes for slow-release systems may open new avenues for treating orthopedic diseases. However, the mechanisms by which lactoferrin regulates bone metabolism remain incompletely understood. This review aims to summarize these mechanisms and highlight recent advances in lactoferrin-derived peptides and their complexed slow-release systems, providing a comprehensive basis for exploring lactoferrin as a potential therapeutic target in bone diseases.